Crashworthiness capability of jute and glass fibre reinforced epoxy tubes under quasi-static loading condition for automotive application - Hamza, Sabah Salim (2021)
During last few years, the interest in using natural fibers as reinforcement in polymers has increased dramatically. Natural fibers are not only strong and lightweight but also relatively very cheap. This study examined the potential utilization of jute in the crash energy absorption. A combination of hand layup and vacuum bladder technique was kused to search the influence of utilizing jute fibre on crashworthiness parameters of composite materials. To improve the mechanical properties, jute fiber was hybridized with glass fiber. In this work, there are two main parts of study. Firstly, it is to investigate the effect of cross-sectional shapes, number of layers and temperature treatment on the progressive deformation of jute/epoxy composite tubes. Secondly, the suitable type of geometry was chosen to study the effect of hybrid (jute-glass/epoxy) onto the structural designs. All the tests were undergone quasi-static axial crushing of 10 mm/min. Their peak load (Pmax), mean load (Pm), energy absorption (EA) and specific energy absorption (SEA) were discussed in detail. In the study of types of five geometrical shapes (corrugated, circular, hexagonal, octagonal and decagonal cross sectional) with different number of layers (two, three and four layers). It is found that the corrugated geometric shape with three layers (RHS) gives the best energy absorption (30.92 J/g) in specific energy absorption parameter compared to other geometries used in present study. For the temperature treatment, the results showed that the post-curing by gradual temperature treatment (TT) improved the peak load by decreased with 55% as compared to similar circular specimen without temperature treatment (No TT). From the test, it is found that the substitution of one layer of jute fibre with one layer of glass fibre resulted in an improvement in the crashworthiness parameters than layers jute. The best result was obtained when hybrid jute-glass was used, where the energy absorption and specific energy absorption was improved by about 43% and 31%, respectively.